2018
DOI: 10.4018/978-1-5225-2956-9.ch003
|View full text |Cite
|
Sign up to set email alerts
|

Shortening the Learning Curve of Media Start-Ups in Accelerators

Abstract: Business accelerators are playing a key role in facilitating the process of new venture creation. Start-ups generally look for the best accelerators to make their long journey short. Media start-ups also look for a supportive mechanism to fasten their start-up experience. In this process, one of the main issues is to shorten their learning curve which is possible by use of start-up accelerators. Therefore, this chapter deals with the idea that which factors are important in this regard. To do so, first, a brie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
6
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 13 publications
(7 citation statements)
references
References 29 publications
1
6
0
Order By: Relevance
“…The two reasons for entrepreneurship used for this study were "having the necessary resources" [19,20,[68][69][70][71] and "difficulty entering the labor market" [25][26][27][28][68][69][70]72,73].…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…The two reasons for entrepreneurship used for this study were "having the necessary resources" [19,20,[68][69][70][71] and "difficulty entering the labor market" [25][26][27][28][68][69][70]72,73].…”
Section: Discussionmentioning
confidence: 99%
“…The search for a source of financing is one of the essential activities of entrepreneurs [21][22][23], but this is not the only one. They must also know the general and specific area and field of business creation, contact networks, and technologies and generate knowledge about them to count on adequate and current machinery, raw materials with the lowest possible cost, services, and a place to operate [18,19]. Obtaining the best option is undoubtedly the most demanding and complicated job of entrepreneurship [24,25].…”
Section: Hypothesis Formulationmentioning
confidence: 99%
See 2 more Smart Citations
“…Furthermore, there are four media divergences of distribution channels, content producers, audiences, and advertisers, which could be the exploitation of entrepreneurial opportunities. Salamzadeh and Markovic (2018) found that accelerators could shorten the learning curve of the media start-ups with seminars and courses, co-working space, divided teams, cohort peers, and mentorship.…”
Section: Introductionmentioning
confidence: 99%